Adekuasi Hemodialisis antara Pasien Menggunakan Akses Catheter Double Lumen (CDL) dengan Akses Arteriovenous Shunt (AV SHUNT) (Journal of Telenursing (JOTING), 2025)
This study aims to determine the difference in hemodialysis adequacy between patients using Catheter Double Lumen (CDL) access with Arteriovenous Shunt (AV Shunt) access in the Hemodialysis Room of Prof. Dr. Margono Soekarjo Purwokerto Hospital. The method used is quantitative, with a bidirectional cohort study design. The study results showed a difference in hemodialysis adequacy between patients using CDL access and patients using AV Shunt access in the Hemodialysis Room of Prof. Dr. Margono Soekarjo Purwokerto Hospital. After the Mann Whitney test was carried out, significant results were obtained, namely p-value = 0.000